Physics-based MCT circuit model using the lumped-charge modeling approach. - Hossain, Z. (IEEE Transactions on power electronics)
This paper presents a physics-based model of metal-oxide-semiconductor (MOS) controlled thyristor (MCT) using the lumped-charge modeling technique. As a relatively new power semiconductor device, little effort has been made thus far in creating an accurate model for simulation use. The only MCT model available to date is that using two bipolar transistors-a behavioral subcircuit model. This model works well for static operation, but has limitations in predicting the dynamic behavior of the device due to the omission of the internal device physics. The use of the lumped-charge modeling technique facilitates the inclusion of internal physical processes and the structural geometry of the device into the model. As a result, this technique provides a more realistic and accurate one-dimensional (1-D) model than any other presently available. This paper presents the successful implementation of the lumped-charge approach on hybrid bipolar-MOS power devices such as the MCT. Most importantly, this model is capable of predicting some dynamic soft-switching behavior of the device, which was never realizable by any SPICE-based simulators. The developed model is thoroughly verified through Saber simulation and experimentation